Waste not want not: LEANer thinking in specialist palliative care units. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Lew, Eva; Gupta, Srirupa; Hare, Caroline; Flynn, Jackie; Cobbin, Mark; Glover, Jan
Abstract : Background: The ability of specialist palliative care units to provide high-quality, patient-centred and cost-effective services within the current economic climate is crucial for both commissioning of services and patient satisfaction.1 Lessons in improving productivity and quality, while minimising cost, can be learned from adopting 'LEAN' thinking.2 In essence, 'LEAN' is an improvement approach which seeks to improve patient flows and eliminate inefficiencies or wastes which are non-value added for the patient, while being open and flexible to change.3 Methods/Aims: Farleigh Hospice engaged external consultants to facilitate a 3 day LEAN workshop to examine the patient pathway from 'referral to bereavement.'4 Only 'frontline' staff participated, for example, Macmillan Nurses/Day Hospice, Triage/Discharge, Administrators/Receptionists, Doctors, Physiotherapists/Occupational Therapists, Psychosocial Team, Bereavement and Carers' Services. Using process mapping investigation, participants visually analysed current pathway steps in 5 areas: referral; initial assessment; intervention; discharge; and, bereavement. Non-value adding activities within the current process were identified. Subsequently, a redesigned 'future state' for services was envisioned resulting in immediate ('Just Do It' projects) and future strategic improvement projects. All redesigned processes were measured for quality, cost and speed of delivery response. Participants committed to long-term project review and progress monitored within further facilitated sessions. Conclusion: Despite the on-going process, benefits already include: Empowered enthusiastic staff with increased likelihood of sustained improvement Less resistance to change Improved acceptability of innovation Improved team working across and within departments Increased time for patient contact Recommendations: 'LEAN' is an effective productivity/quality improvement tool which can be successfully applied within SPC units.